Kemurahan Tuhan dalam kitab Yunus: telaah Teologis dan Etis - Rini; Refamati Gulo (Sekolah Tinggi Teologi Injili Indonesia Ambon, 2026)
This study explores the theological message of the Book of Jonah, especially related to the prophet’s flight, God’s mercy, and the meaning of the second chance granted by God to both Jonah and Nineveh. The research is motivated by the observation that many previous studies emphasize the narrative and moral dimensions of Jonah, while the theme of divine mercy and universal salvation has not been systematically examined as a coherent theological framework. Using a qualitative approach with narrative-theological analysis, this study reads the Book of Jonah as a prophetic narrative that reveals God’s sovereignty, love, and inclusive mission for all nations. The analysis shows three main findings. First, Jonah’s futile attempt to flee demonstrates that human disobedience cannot thwart God’s sovereign plan, because God can use natural events and human decisions to bring His servant back to obedience. Second, God’s mercy is revealed in a universal way, not only to rebellious Jonah but also to the violent city of Nineveh, indicating that God’s saving will reaches beyond Israel. Third, the second chance given to Jonah and Nineveh expresses restorative grace that calls for genuine repentance and concrete obedience. Theologically, the Book of Jonah affirms that God’s mercy is universal and becomes a critical foundation for the church’s inclusive mission and ethical attitude toward “the other” in today’s plural society.